2020
DOI: 10.1186/s13033-020-00420-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and drivers to capacity-building in global mental health projects

Abstract: Background The global shortage of mental health workers is a significant barrier to the implementation and scale-up of mental health services. Partially as a result of this shortage, approximately 85% of people with mental, neurological and substance-use disorders in low- and middle-income countries do not receive care. Consequently, developing and implementing scalable solutions for mental health capacity-building has been identified as a priority in global mental health. There remains limited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The framework was populated separately and discussed, using an iterative process, to arrive at consensus about predominant themes. This paper presents findings for the Service Delivery cluster, with results from the other two clusters published elsewhere in this volume [13,14].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The framework was populated separately and discussed, using an iterative process, to arrive at consensus about predominant themes. This paper presents findings for the Service Delivery cluster, with results from the other two clusters published elsewhere in this volume [13,14].…”
Section: Discussionmentioning
confidence: 88%
“…A major challenge in the implementation of mental health detection was the lack of appropriate human resources. As described further by Endale et al [13] in an accompanying paper, this was related to barriers in retaining providers, stigma associated with working in mental health services, and the absence of specialists needed to conduct diagnostic evaluations.…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper describes results of a qualitative analysis of barriers and drivers to stakeholder engagement in GMH as part of a multi-methods study examining barriers and drivers to implementation across a portfolio of GCC-funded projects [ 21 – 23 ]. Based on the results of a quantitative analysis of GCC-funded project outcomes using a portfolio-level Theory of Change framework [ 24 ], six key themes emerged as important to implementation success: (1) stakeholder engagement; (2) training providers; (3) supervision of providers; (4); detection of mental illness; (5) treatment of mental illness, and; (6) mental health promotion and awareness.…”
Section: Methodsmentioning
confidence: 99%
“…Each of three members of the study team (JM, OQ and TE) initially identified themes, and subsequently discussed and refined them until consensus was achieved. This paper presents findings for the stakeholder engagement cluster, with results from the other two clusters published as part of this series [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%